RELASI ELITE POLITIK DENGAN MEDIA (STUDI REPRESENTASI PROSES PENCALONAN AHOK SEBAGAI CALON GUBERNUR DI PILKADA DKI JAKARTA 2017 DI TEMPO.CO) - Ali Imron Hamid; Udi Rusadi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Abstract Objective : (1) to find the relation between Ahok with the media and how far Ahok use the media in getting public support to advance further in the nomination of the governor in the 2017 elections; (2) to explore how media Ahok utilize in order to get the number of readers or visitors is high and thus can get revenue from advertising (3) to analyze how the strategy of media in producing news, especially about Ahok so they can get revenue(4) to uncover what interests were behind the relationship between the media Ahok. Method : critical discourse analysis. Results: based on the results of the study found a relation between Ahok with the media in order to support the nomination process as Governor of Jakarta at the local elections in 2017. Media utilizes Ahok to get high visitor from some news about Ahok.The strategy that media do is make controversy news of Ahok and some news about his leadership in managing Jakarta. Both relations between Ahok and media are economicinterest and political image. Conclusion: News about Ahok in the media is to increase his political image in public. And media using Ahok for economic purposes.